Cryptocurrency Mining For Dummies - Kent, Peter; Bain, Tyler (--For dummies., 2019)
Find out the essentials of cryptocurrency mining The cryptocurrency phenomenon has sparked a new opportunity mine for virtual gold, kind of like the prospectors of a couple centuries back. This time around, you need some tech know-how to get into the cryptocurrency mining game. This book shares the insight of two cryptocurrency insiders as they break down the necessary hardware, software, and strategies to mine Bitcoin, Ethereum, Monero, LiteCoin, and Dash. They also provide insight on how to stay ahead of the curve to maximize your return on investment. Get the tech tools and know-how to start mining Pick the best cryptocurrency to return your investment Apply a sound strategy to stay ahead of the game Find cryptocurrency value at the source From the basics of cryptocurrency and blockchain to selecting the best currency to mine, this easy-to-access book makes it easy to get started today!